2018
DOI: 10.1007/s00404-018-4748-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-operative glove changing during cesarean section on post-operative complications: a randomized controlled trial

Abstract: Intra-operative glove changing prior to abdominal closure during cesarean section significantly reduced the incidence of post-operative wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 13 publications
3
40
0
Order By: Relevance
“… 4 Although one recent RCT reported a decreased risk of a composite wound complication with glove change, three previous trials found no benefit to glove change, including the largest (N=760, relative risk [RR] for endometritis 1.0, 95% CI 0.79–1.3). 69 72 Given this inconsistent and conflicting data, routine glove change is not recommended.…”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“… 4 Although one recent RCT reported a decreased risk of a composite wound complication with glove change, three previous trials found no benefit to glove change, including the largest (N=760, relative risk [RR] for endometritis 1.0, 95% CI 0.79–1.3). 69 72 Given this inconsistent and conflicting data, routine glove change is not recommended.…”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“…Characteristics of included studies. Five studies were published in peer-reviewed journals [21][22][23][24][25] . One included study was available only in an academic search engine 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Five included studies were undertaken in the United States, whereas the remaining included study was conducted in India. One included study recruited only women who underwent elective CS 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations